Knowing their place: Feminist understandings and perceptions of women adult educators in museums. Issue 2 (November 2016) - Clover, Darlene E.; Sanford, K
Arguing gender inequity remains one of the biggest challenges of our time, and framed within the concept of 'pedagogic contact zones', our article shares findings from a five-year feminist, cross-national study of women adult educators and community practitioners in public museums and art galleries in Canada and the United Kingdom. Findings show a general lack of feminist consciousness and pedagogical skills amongst these women, problematic essentialist depictions of women educators that contrast portrayals of curators, and an equation of feminism with 'bias'. Yet there is a growing number of women who identify as feminists and take up women's issues in a variety of ways. Museums have the ability to be sites of feminist adult education and make contributions to gender struggle.